Noninvasive assessment of radiation-induced renal injury in mice. (4th May 2021) - Ahmad, Anis; Shi, Junwei; Ansari, Saba; Afaghani, Jumana; Molina, Judith; Pollack, Alan; Merscher, Sandra; Zeidan, Youssef H.; Fornoni, Alessia; Marples, Brian
Abstract: Purpose: The kidney is a radiosensitive late-responding normal tissue. Injury is characterized by radiation nephropathy and decline of glomerular filtration rate (GFR). The current study aimed to compare two rapid and cost-effective methodologies of assessing GFR against more conventional biomarker measurements. Methods: C57BL/6 mice were treated with bilateral focal X-irradiation (1x14Gy or 5x6Gy). Functional measurements of kidney injury were assessed 20 weeks post-treatment. GFR was estimated using a transcutaneous measurement of fluorescein-isothiocyanate conjugated (FITC)-sinistrin renal excretion and also dynamic contrast-enhanced CT imaging with a contrast agent (ISOVUE-300 Iopamidol). Results: Hematoxylin and eosin (H&E) and Periodic acid-Schiff staining identified comparable radiation-induced glomerular atrophy and mesangial matrix accumulation after both radiation schedules, respectively, although the fractionated regimen resulted in less diffuse tubulointerstitial fibrosis. Albumin-to-creatinine ratios (ACR) increased after irradiation (1x14Gy: 100.4 ± 12.2 µg/mg; 6x5Gy: 80.4 ± 3.02 µg/mg) and were double that of nontreated controls (44.9 ± 3.64 µg/mg). GFR defined by both techniques was negatively correlated with BUN, mesangial expansion score, and serum creatinine. The FITC-sinistrin transcutaneous method was more rapid and can be used to assess GFR in conscious animals, dynamic contrast-enhanced CT imaging technique was equally safe and effective. Conclusion: This study demonstrated that GFR measured by dynamic contrast-enhanced CT imaging is safe and effective compared to transcutaneous methodology to estimate kidney function.